Outline of Biological Effects, Fecundity, Eclosion and Lifespan on Adult Tropical Warehouse Moth, Cadra cautella (Lepidoptera: Pyralidae) by using Sex Ratio - Juma Khan; Mehmood Ali Noor (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2016)
Tropical warehouse moth Cadra cautella Walker, 1863 (Lepidoptera: Pyralidae) is a major pest of stored food products worldwide. It is originated from the tropics and subtropics but it disperses through imported food cargoes. The biological performance, fecundity, eclosion (emergence of larvae from egg or adult from pupae) and lifespan of adult Tropical warehouse moth at different sex ratio (female: male) was studied under constant conditions. Fecundity and eclosion larvae investigated by fi ve treatments: sex ratio (1F:1M, 2M, and 3M), (1M: 2F, 3F) and one more treatment of separated male and female as a control for lifespan. Eclosion adult measured by collecting 350 pupae in different aged 200 male and 150 female. 1M: 3F treatment have the highest number of eggs and the least percentage of hatching to larvae and 2M: 1F and 3M: 1F treatments non-signifi cantly behaved between them having the least number of total eggs and the maximum number at total eggs per female, in both have a larger percentage of hatching to larvae respectively. Lifespan of male was signifi cant with all treatments except 1M: 3F and lifespan of female was non-signifi cant with all treatments. Eclosion of adults calculated as three levels of normal, abnormal and not emerged; for female 42% normal, 5% abnormal, 53% not emerged out of 150 pupae and for male 20% normal, 10% abnormal 70% not emerged out of 200 pupae.